Investigation of the role of the DNA-modifying enzyme, activation-induced cytidine deaminase (AID), in cancer - Godsmark, Grant Kenneth (Division of Clinical Haematology, 2016)
The DNA-editing enzyme, Activation-Induced cytidine Deaminase (AID) is essential for antibody diversification and plays an important role in immunity. AID is specifically expressed in activated B-cells and mutates targeted DNA sites, diversifying the antibody repertoire. Due to its mutagenic nature, AID expression is tightly regulated, however, its overexpression has been associated with translocation of the c-MYC oncogene, a characteristic of the B-cell derived cancer, Burkitt's lymphoma (BL). Although currently uncharacterised, AID overexpression has also been implicated in non-lymphoid cancers including prostate, liver and colon. The function of AID in the oncogenic process is not well defined and therefore this project is aimed at using cell culture models to study the function of AID in cancer. AID mRNA and protein expression levels were determined in five cell lines of B-cell origin, and 16 epithelial cell lines (colon, prostate, head and neck and oesophageal). While AID expression was easily detected in the B-cell derived cell lines, no significant expression of both AID mRNA and protein expression was found in all the epithelial derived cell lines. The B lymphoblastoid cell line, L1439A, which is derived from a healthy donor, and harboured relatively low AID expression, was originally selected for ectopic expression of AID. Transfection of this cell line using conventional methods and lipid and polymer based transfection reagents was not successful, and therefore, nucleofection was used, which caused successful uptake of the AID-expressing plasmids as well as corresponding controls. However, this method was too harsh for the L1439A cell line as it did not survive post-nucleofection. Based on this result, the BL cell line Ramos, which expresses relatively low AID compared to the other BL cell lines used in the screen, was selected as an alternative. Plasmids constitutively expressing AID, as well as their corresponding empty vector, were successfully introduced into these cells using an established nucleofection protocol. While cells containing the empty vectors could be selected and expanded in culture, cells overexpressing AID underwent apoptosis approximately three days post-transfection. This is likely due to the highly mutagenic nature of the enzyme. As an alternative approach to studying the function of AID in cancer, a knockdown approach was taken, using siRNA.